2010
DOI: 10.1007/s10308-010-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

EU perceptions in Northeast Asia: a cross-national comparative study of press coverage and citizens’ opinion

Abstract: This study provides a unique and innovative comparative investigation of the press coverage and citizens' opinion towards the European Union (EU) and its bilateral relations with the three most important Northeast Asian countries, People's Republic of China, Japan and South Korea. On the basis of media content analysis of mainstream national newspapers and opinion surveys of the general public and elite stakeholders, the analysis explores the extent to which media agenda and framing, the shared interests betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…On EU–China energy issues, past research showed that the EU's environment and energy role was almost invisible in the Chinese mainstream media (Chaban and Holland, 2014; Zhang, 2010), and more recent analysis indicates that China has yet to view the EU as a prominent global energy player or a major energy partner (Lai and Shi, 2017). These findings are mainly based on traditional media analysis and interviews with China's elite.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On EU–China energy issues, past research showed that the EU's environment and energy role was almost invisible in the Chinese mainstream media (Chaban and Holland, 2014; Zhang, 2010), and more recent analysis indicates that China has yet to view the EU as a prominent global energy player or a major energy partner (Lai and Shi, 2017). These findings are mainly based on traditional media analysis and interviews with China's elite.…”
Section: Theoretical Frameworkmentioning
confidence: 99%